Factors associated with Q fever vaccination in Australian wildlife rehabilitators. Issue 1 (4th January 2023) - Mathews, Karen O.; Norris, Jacqueline M.; Phalen, David; Malikides, Nick; Savage, Cathie; Sheehy, Paul A.; Bosward, Katrina L.
Highlights: Australian wildlife rehabilitators (AWR) demonstrated shortfalls in Q fever vaccine uptake despite being at increased risk of developing Q fever. Vaccinated AWR were significantly more likely to be ≤ 50 years, have university-level education, have attended an animal birth, and reside in New South Wales/Australian Capital Territory and Queensland. Barriers to Q fever vaccination (QFV) in unvaccinated AWR included lack of Q fever knowledge, complacency, convenience of vaccination and concerns regarding the safety, efficacy, and importance of QFV. Multidisciplinary educational interventions regarding the potential health consequences of C. burnetii exposure and prevention of Q fever in AWR are required. Improving the affordability and accessibility of QFV may also increase vaccine uptake in AWR. Abstract: Australian wildlife rehabilitators (AWR) are at risk of contracting Q fever, a serious zoonotic disease caused by Coxiella burnetii . Despite Australian government recommendations for AWR to receive Q fever vaccination (QFV), and the availability of a safe and effective vaccine in Australia, shortfalls in vaccine uptake have been observed in AWR. This study aimed to determine factors associated with QFV status and describe AWR attitudes and potential barriers towards QFV. Data were obtained from a nationwide, online, cross-sectional survey of AWR undertaken in 2018. Approximately-three quarters (200/265; 75.5 %) of those that had heard of Q fever were also aware of the Q fever vaccine, and of those, 25.5 % (51/200) were vaccinated. Barriers to QFV, among unvaccinated respondents who had also heard of Q fever and the vaccine (149/200; 74.5 %), included concerns regarding the safety, efficacy, and importance of the Q fever vaccine. Complacency toward vaccination, convenience of vaccination, and a lack of Q fever knowledge were also notable barriers. Only 27.7 % (41/148) of respondents reported having had vaccination recommended to them. Multivariable logistic regression identified that vaccinated AWR were more likely to be aged ≤ 50 years (OR 4.51, 95 % CI: 2.14–10.11), have had a university level education (OR 2.78, 95 % CI: 1.39–5.73), have resided in New South Wales/Australian Capital Territory and Queensland than in other Australian jurisdictions (OR 2.9, 95 % CI: 1.10–8.83 and OR 4.82, 95 % CI: 1.64–16.00 respectively) and have attended an animal birth (OR 2.14, 95 % CI: 1.02–4.73). Knowledge gaps regarding Q fever and QFV in AWR demonstrated the need for interventions to raise the awareness of the potential health consequences of C. burnetii exposure and Q fever prevention. Education programs to allow AWR to develop an informed perspective of Q fever and QFV, coupled with improvements in vaccine affordability and the implementation of programs to enhance accessibility, may also increase vaccine uptake.